2016
DOI: 10.1111/cen.13106
|View full text |Cite
|
Sign up to set email alerts
|

Maternal total T4 during the first half of pregnancy: physiologic aspects and the risk of adverse outcomes in comparison with free T4

Abstract: Maternal TT4 levels are highly variable in the first half of pregnancy and are poorly related to maternal TSH. This study shows that maternal TT4 levels are either not associated, or not better associated as compared to FT4, with adverse pregnancy or child outcomes. This suggests that the maternal TT4 is inferior to FT4 in the assessment of maternal thyroid function during the first half of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
2
29
5
Order By: Relevance
“…The presence of TAI is the most important cause of high serum TSH levels and SCH, and therefore, we excluded in this study women with TAI in order to investigate the impact of variation on serum TSH levels within the normal (non-pregnant) range on pregnancy outcomes (19,20). Serum TSH levels were strongly correlated with FT4 levels, conforming the reliability of FT4 during the first trimester of pregnancy, as it has also been shown in the study by Korevaar and coworkers, in which pregnancy outcomes were better correlated with FT4 than with total T4 (21). Due to the exclusion of women with TAI, a left-shifted TSH distribution was observed with 90% of women having TSH levels <2.5 mIU/L.…”
Section: Discussionsupporting
confidence: 56%
“…The presence of TAI is the most important cause of high serum TSH levels and SCH, and therefore, we excluded in this study women with TAI in order to investigate the impact of variation on serum TSH levels within the normal (non-pregnant) range on pregnancy outcomes (19,20). Serum TSH levels were strongly correlated with FT4 levels, conforming the reliability of FT4 during the first trimester of pregnancy, as it has also been shown in the study by Korevaar and coworkers, in which pregnancy outcomes were better correlated with FT4 than with total T4 (21). Due to the exclusion of women with TAI, a left-shifted TSH distribution was observed with 90% of women having TSH levels <2.5 mIU/L.…”
Section: Discussionsupporting
confidence: 56%
“…Additional uncertainty arises from an ongoing controversy, if levels of total (264) or free thyroid hormones (401, 402), measured either via immunoassays (403) or LC/tandem mass spectrometry (404), are the preferred targets for diagnostic interpretation (248, 405). There is no doubt, however, that laboratory investigations must always be accompanied by careful clinical evaluation of the patient’s symptoms and history (401).…”
Section: Methods Of Assessment and Differential Diagnosismentioning
confidence: 99%
“…Five studies presenting regression analyses were excluded 26,29,30,35,45 because they did not provide regression information in a form that would allow straightforward conversion into odds ratios: for example, 2 studies 29,30 provided linear regression results with continuous not binary predictors. A further 8 articles were excluded from the meta-analysis for the following reasons: sibling papers with no additional data (n = 2), 21,51 lacking numerical data (n = 1), 44 using a novel outcome measure that was not validated or suitable for meta-analysis (n = 1), 34 reporting odds ratios (using logistic regression) but using continuous predictors (n = 1) 39 and reporting psychomotor outcomes only (n = 3). 19,24,42 Details on why studies were excluded from the meta-analysis are shown in Table S5.…”
Section: Observational Studies Excluded From Meta-analysismentioning
confidence: 99%